(untitled) (Research, Society and Development, 2020)
Objective: evaluate the health behavior and nutritional profile of hypertensive elderly enrolled in the Hiperdia program. Method: cross-sectional study conducted with 60 hypertensive elderly. Data were collected through interviews and anthropometric evaluation. For the interview, a semi-structured form was used that included sociodemographic variables related to health behavior between November and December 2017. Results: reporting to eating habits, the most consumed food was mass. The rate of alcohol consumption and smoking was low (8.3% and 13.3%) Respectively. Regarding body mass index, 53.0% of the elderly were eutrophic, however, there was a prevalence of abdominal obesity, with a high risk for cardiovascular diseases in females (48.3%). Conclusion: the evaluation of health behavior and nutritional status of hypertensive elderly is crucial for the prevention of complications and comorbidities.